(3GdHGQY aj CMcGe GdfLhes - (3GdTjHGfj , Ydj Hf CHj GdQLGdj GdTjHGfj GdeZQHj GdbjQhGfj, CHh GdMSf,J (B432 (3g` s
(3ChdgG (B:s
(3bGd Ydj GdMeO ddg GdhGMO GdbgGQ gPG cJGH LeYJ ajg eYGfj Yde GdfLhe hZQGFH CSQGQgG , hGNJQJg ef cKjQ ef cJH YdeGFgG hCVaJ Edjg eG acQJi , hCJJ Ydjg JLQHJi s
(3BNQgG (B:s
(3Ke jchf HYO Pdc bJGd TOjO Ch Ef CfbU ef GdMhJ aEf Gdedc hjchf SdGeI HbGFg hcKQI CeWGQg hGddg CYde HGdUhGH s
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3jJab ChdgG eY Chd GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX hGdYHGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B92s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs